Clinical prediction model and 2-year mortality for multiple organ dysfunction in patients aged 80 years or older following hip fracture surgery: a prospective cohort study - Lei Liu; Yang Deng; Zhijun Qin; Ying Zhang; Xi Yang; Ji Feng; Chenzhu Yin (Frontiers in Medicine)
BackgroundThe prediction of postoperative complications is vital in the management of hip fracture. This study specifically examined the occurrence of multiple organ dysfunction syndrome in the elderly (MODSE) following hip fracture surgery and explored its predictive model and correlation with long-term mortality.MethodsThis prospective cohort study included all patients aged 80 years and older who underwent hip fracture surgery at a tertiary orthopedic hospital between January 2020 and March 2021. The patients were categorized into the MODSE and non-MODSE groups. The pre, peri, and postoperative variables were retrospectively screened to establish and validate prediction model for MODSE. The patients were subsequently followed up prospectively until 2 years after discharge in order to explore the association between MODSE and long-term mortality.ResultsSignificant discrepancies in clinical characteristics were observed between MODSE and non-MODSE patients. Those with a preoperative age-adjusted Charlson Comorbidity Index > 5, Impaired swallowing, an Acute Physiology and Chronic Health Evaluation II score ≥ 12 within the initial 24 h post-surgery, prothrombin time > 14 s, along with high-sensitivity cardiac troponin T > 14 pg./mL and procalcitonin levels > 0.25 ng/mL on the first day after surgery were found to have a higher likelihood of developing MODSE. Moreover, the presence of MODSE correlated with a 3.13-fold and 2.88-fold increased risk of mortality at 1 and 2 years post-discharge, respectively.ConclusionPredicting postoperative MODSE in elderly hip fracture patients is essential and feasible, as its occurrence represents poor outcome during hospitalization and predicts heightened long-term mortality rates.